Update Chapter English Language Learning Using Social Media - Evi Mahsunah (Department of English Language Education, UIN Sunan Ampel Surabaya, 2017)
This study explores the changing students’ habit update status in social media into update chapter to increase their achievement in English. It is a learning strategy in English language teaching and learning using social media technology. The aim is to motivate students more active to read their literature and then share and discuss their reading in social media. The students not only have to update their chapter in reading, but also have to give comment or respond to their friends update. So, this strategy makes the students discuss their lesson more than usual. This study uses questioner and documentation technic to collect the data. Based on the data, it is known that students are already using social media for purposes that include the social and the educational. Update chapter make them using this technology in class/after class. Social media brings learning outside the classroom autonomous, independent, motivational and fun. Therefore, the students‘achievement in English language teaching and learning also increases significant.